Financing for Gender Equality : Results and Good Practices - Kim, Jim Yong (2016)
Remarks delivered by Jim Yong Kim, President of the World Bank Group. The Third International Conference on Financing for Development represents an important milestone in efforts to achieve universal and sustainable development as we move beyond 2015 and introduce a new set of Sustainable Development Goals. This event aims to mobilize high-level political support for financing gender equality and women’s empowerment, drawing on global good practices. He discusses the array of financing sources—private, public, domestic, and international—and policy changes needed to realize the vision of transformative gender equality and women’s empowerment.